Efficacy of public financial management in reducing crime against children: Empirical evidence from subnational governments in India - Jitesh Yadav; Lekha Chakraborty (Levy Economics Institute of Bard College, 2022)
Public financial management (PFM) has a significant role in linking resources to results by financing human development outcomes. When economic stimulus packages are short run in nature, thematic PFM, such as child budgeting, has a crucial role in reducing crime against children. Using fixed effects models, we explore the determinants of reduced crime against children. The PFMrelated variables are found to have greater impact than economic growth per se in tackling crime against children. Capital expenditure in the social sector is found to be inversely related to crimes against children, though mere allocation in social sector budgets is not found to be effective in reducing crime rates. Specific PFM tools, like child budgeting, need to be analyzed for their role in child protection services. In India, child budgeting has been introduced in states where the rates of crime against children are also high. To understand the efficacy of child budgeting in reducing crime rates, the year of inception (year in which the child budgeting was introduced in the state) of children budgeting in a state is incorporated in the panel models. The coefficients reveal that years of inception and crime against children are inversely related, reinforcing the effectiveness of PFM tools such as child budgeting in reducing crimes. The existence of a positive link between social expenditure and the incidence of crime is at first counterintuitive, but a closer examination reveals a nonlinear relationship between crime incidence and social spending, which is revealed from the statistically significant negative squared term.
Keywords: C33; H00; H5; J13; 330; Public Financial Management; Child Budgeting; Social Spending; Child Protection